1993
DOI: 10.1007/bf00878511
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenicity of antiarrhythmic drugs and intraventricular conduction disorders: Possible aggravation by myocardial ischemia?Study in the porcine in situ heart

Abstract: The effects of three antiarrhythmic drugs were investigated in anesthetized, open-chest pigs, in a left ventricular area, under pacing at a constant high rate (180 beats/min), in the absence and presence of ischemia. Ischemia was produced by transient complete occlusion of the left anterior descending coronary artery near its origin. In addition to the surface electrocardiogram, conduction time and monophasic action potential were recorded in the contractile fibers. In the absence of ischemia, intravenous flec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The results obtained from the EFT measurement for evaluating vulnerability to fibrillation are consistent with those of other methods such as the determination of the time to onset of ischaemia‐induced fibrillation (Timour et al , 1991; Aupetit et al , 1993b; Loufoua et al , 1993). Ischaemia both shortens the time to fibrillation in proportion to its severity and hastens the fall of EFT: vulnerability to fibrillation may thus be considered to be inversely correlated to EFT or time to fibrillation.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results obtained from the EFT measurement for evaluating vulnerability to fibrillation are consistent with those of other methods such as the determination of the time to onset of ischaemia‐induced fibrillation (Timour et al , 1991; Aupetit et al , 1993b; Loufoua et al , 1993). Ischaemia both shortens the time to fibrillation in proportion to its severity and hastens the fall of EFT: vulnerability to fibrillation may thus be considered to be inversely correlated to EFT or time to fibrillation.…”
Section: Discussionsupporting
confidence: 83%
“…The increase in mortality in multicentre trials performed in post‐infarction management (CAST, 1989; 1991) has justified this caution. Lastly, experimental studies have confirmed the possible harmful effects of such drugs under conditions of myocardial ischaemia, seen particularly as a reduction in the time to fibrillation (Timour et al , 1991; Aupetit et al , 1993b; Loufoua et al , 1993), almost immediately after their intravenous injection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The contractile fibers possessing the most negative potential exhibit the most delayed activation. The behavior of bupivacaine resembles that of the IC antiarrhythmic drugs, such as flecainide (21)(22)(23)(24)(25), which depress intraventricular conduction to a great extent on account of a strong influence on sodium channel in moderate doses which have little effect on repolarization. As these drugs have been shown by multicenter, randomized, placebo-controlled trials (26,27) to be likely to increase the incidence of sudden death, instead of decreasing it as expected, similar accidents were possible with bupivacaine.…”
Section: Discussionmentioning
confidence: 99%